2013
DOI: 10.4236/jdm.2013.33023
|View full text |Cite
|
Sign up to set email alerts
|

Importance of regional differences in the features of type 2 diabetes mellitus in one and the same country—The example of Thailand

Abstract: Background: A dataset from a nationwide assessment of type 2 diabetes mellitus (T2DM) patients from Thailand was reassessed. Objective: Prevalence of T2DM is highest in the northeast of Thailand and the intention of the study was to assess whether the clinical picture and behavior of patients from the northeast differ from the rest of the country. Materials and Methods: The variables of two groups of patients i.e. those from the northeast of Thailand and patients from the remaining three other regions, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This might not be necessarily because of T2DM but could be the effect of a recall bias or the similar dietary habits of family members, 9 especially in a region where glutinous rice is a staple food and is known to have a high glycemic index and where the prevalence rate of T2DM is higher than in other regions of the country. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…This might not be necessarily because of T2DM but could be the effect of a recall bias or the similar dietary habits of family members, 9 especially in a region where glutinous rice is a staple food and is known to have a high glycemic index and where the prevalence rate of T2DM is higher than in other regions of the country. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…In Northeast Thailand, surveys conducted from 2005-2006 revealed that diabetes-related mortality rates were the highest in the country [4]- [6]. We reviewed department documentation on diabetic patients admitted with hypoglycemia in a community hospitalization a 120-bed in Northeast Thailand in 2008-2011.…”
Section: Introductionmentioning
confidence: 99%